Patterns of Maxillofacial Injures Caused by Motorcycle Accidents - Noorali, Imad S.; Attyia, Marwa A.; Alsunbuli, Mudher M. B. (International Archives of Otorhinolaryngology, 2023)
Introduction Motorcycles are used as a common means of transportation, and motorcycle accidents are responsible for a major portion of trauma injuries.Objectives The purpose of this study was to analyze the patterns of facial injuries in motorcyclists, to evaluate the types of injuries, and to investigate if the accident-related factors had any impact on the characteristics of the injuries.Methods This retrospective observational study included 74 patients with maxillofacial injuries following motorcycle-related accidents. Investigated data were divided into four main categories: sociodemographic, accident-related, injury-related, and treatment-related.Results All the patients were males with a mean age (±SD) of 25.03 (±9.986) years. Most accidents (n = 44, 59.4%) occurred in the evening. Most of the patients (n = 40, 54%) were traveling on motorcycle models that had maximum speed of over 120 km/h. Furthermore, 15 patients (18.9%) were under the influence of alcohol during the crashes and only one patient was wearing a helmet. Fractures of the maxillofacial bones were observed in 50 (67.5%) crash victims; 24 of them (48%) had middle third fractures, 11 (22%) had mandibular fractures, and 15 patients (30%) presented with a combination of lower, middle, and upper third fractures.Conclusion Almost all patients were not wearing helmets at the moment of the crash. The most common fractured site was the maxilla. The majority of the patients received surgical treatment. Increased enforcement of safety measures for riders and raising awareness about the dangers of motorcycle crashes are required measures to improve traffic safety and, ultimately, population health.
Keywords: maxillofacial injuries; head protective devices; motorcycles; accidents; traffic